Water quality at Setiu Wetland, Terengganu, Malaysia - Wahid, Mohamad Faiz (2021)
Setiu Wetlands in Terengganu is one of the most beautiful wetlands in Malaysia with pristine white beaches, rich in mangroves biodiversity, tranquil rivers, and beautiful nature parks. The estuarine lagoon system is rich in natural capital and if systematically managed, it will sustainably provide resources for agriculture, aquaculture, eco-tourism, and recreational activities and benefited the local communities. Urbanization and industrialization pose ecological risks to the fauna and flora of the wetlands. Once the ecosystem is disturbed; the wetlands and its invaluable treasures will be destroyed and may come to extinction. A study on characteristics and status of water quality at two different rivers was conducted: Ular River and Setiu River. Ular River was an oil palm plantation area while Setiu River was an aquaculture and ecotourism development area. This study was conducted to determine and compare the quality level of water of the two rivers, especially during low and high tides. A total of 108 water samples were collected at three (3) different sampling station (S1, S,2 and S3) in four (4) different months from September 2018 to November 2019 during low and high tides condition. In-situ data included Temperature; Conductivity; Dissolved Oxygen (DO), pH and Turbidity were recorded. Ammoniacal Nitrogen (NH3-N), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) were conducted in laboratory. The Water Quality Index (WQI) was calculated based on six (6) water quality parameters namely Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Ammoniacal Nitrogen (AN) and Total Suspended Solid (TSS) was representative of the state of water quality at study area. The parameters measured showed lower mean values of surface salinity, temperature, DO, pH and TSS during the wet season relative to dry season. Besides, the concentration of BOD was high during the wet season and lower in the dry season. At last, water quality for the Setiu Wetland was highly influenced by anthropogenic activities and seasonal variation. Therefore, both factors must be focused to move towards proper management of this wetland.